2022
DOI: 10.1038/s41598-022-06702-w
|View full text |Cite
|
Sign up to set email alerts
|

Simple methods for quantifying super-resolved cortical actin

Abstract: Cortical actin plays a key role in cell movement and division, but has also been implicated in the organisation of cell surface receptors such as G protein-coupled receptors. The actin mesh proximal to the inner membrane forms small fenced regions, or ‘corrals’, in which receptors can be constrained. Quantification of the actin mesh at the nanoscale has largely been attempted in single molecule datasets and electron micrographs. This work describes the development and validation of workflows for analysis of su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
5
10
0
Order By: Relevance
“…Cortical actin is typically defined as a thin layer of dense actin filaments in close proximity (approximately 10-20 nm) to the plasma membrane of the cell 46,47 and forming a mesh of small fenced regions (termed corrals) within which membrane and/or cytoplasmic proteins/organelles can become transiently trapped 48 . Phalloidin, typically used to label cortical actin in cells, lacks amine groups for gel anchoring: to tackle this issue and retain the fluorescence signal after expansion, in the first step fluorophore-conjugated phalloidin was labeled using anti-fluorophore antibodies, followed by hydrogel synthesis, enzymatic digestion, and expansion (see Materials and Methods for more details).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cortical actin is typically defined as a thin layer of dense actin filaments in close proximity (approximately 10-20 nm) to the plasma membrane of the cell 46,47 and forming a mesh of small fenced regions (termed corrals) within which membrane and/or cytoplasmic proteins/organelles can become transiently trapped 48 . Phalloidin, typically used to label cortical actin in cells, lacks amine groups for gel anchoring: to tackle this issue and retain the fluorescence signal after expansion, in the first step fluorophore-conjugated phalloidin was labeled using anti-fluorophore antibodies, followed by hydrogel synthesis, enzymatic digestion, and expansion (see Materials and Methods for more details).…”
Section: Resultsmentioning
confidence: 99%
“…For the calculation of the MT opening (number and average area), the binary images were analyzed by MorphoLibJ plugin (Plugin˃MorphoLibJ˃Segmentation˃Morphological Segmentation˃Border Image). To provide a way of characterizing the intensity distribution of the MT network in terms of branches’ average distance and number of intensity peaks, an adaptation of Garlick’s method 48 was implemented in Python 3.6. Such features were calculated through an image-processing algorithm plotting intensity values along 175 diameters running across the circle inscribed in every square image.…”
Section: Methodsmentioning
confidence: 99%
“…(6) As a complex dynamic filamentous network throughout the whole cell, it would be interesting to reveal the real-time dynamic changes in the cytoskeleton and the ultrastructural characterization of pathogen and host responses during the interaction. The recent application of high-spatiotemporal-resolution imaging techniques and volume imaging systems [ 114 , 115 , 116 ] will help us better understand the cytoskeleton remodeling and function during the plant defense response. Recently, Vernet et al successfully observed the nematode–root interactions in tomato using light sheet fluorescence microscopy (LSFM) and optical projection tomography (OPT) [ 117 ].…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…30−32 The first strategy involves synthesizing a trivalent phalloidin linker (termed TRITON), which contains rhodamine B (Rh B), phalloidin and an acryloyl unit (monomer) for gel-grafting to enable visualization of actin filaments after expansion. 30,33 The second strategy, proposed by Park et al, uses antifluorophore antibodies to stain the fluorophore of phalloidin conjugates, and demonstrated ExM imaging of actin filament organization using the original ExM procedure. 32 The third strategy, proposed by Trinks and co-workers, involves staining F-actin with a biotinylated phalloidin conjugate (phall-XX-biotin), followed by conjugation with fluorescently labeled streptavidin, in which streptavidin can provide lysine residues to introduce polymerizable moieties for gel-anchoring.…”
mentioning
confidence: 99%
“…Actin is one of the most abundant proteins in eukaryotic cells and plays a vital role in cellular structure and functions, such as maintenance of cell morphology, cell motility, cell division, , transcriptional regulation, , endocytosis, intracellular trafficking, and muscle contraction . Therefore, visualization of actin filaments using ExM has also garnered significant interest. However, due to the lack of an anchorable unit in commonly used phalloidin conjugates, retention of phalloidin labels remains challenging using the original ExM protocol. , To overcome this limitation, three phalloidin-actin complex anchoring strategies have been developed (Figure ). The first strategy involves synthesizing a trivalent phalloidin linker (termed TRITON), which contains rhodamine B (Rh B), phalloidin and an acryloyl unit (monomer) for gel-grafting to enable visualization of actin filaments after expansion. , The second strategy, proposed by Park et al, uses antifluorophore antibodies to stain the fluorophore of phalloidin conjugates, and demonstrated ExM imaging of actin filament organization using the original ExM procedure .…”
mentioning
confidence: 99%